Keeping up with the Joneses: A field study of the relationships among upward, lateral, and downward comparisons and pay level satisfaction - HARRIS, Michael M. (Institutional Knowledge at Singapore Management University, 2008)
The authors examined the relationship between the direction of pay comparisons and pay level satisfaction. They hypothesized that upward pay comparisons would significantly predict pay level satisfaction, even when controlling for other comparisons. Results reported in 2 samples (U.S. sample, N = 295; Belgian sample, N = 67) generally supported this hypothesis. Analyses showed that individuals who were paid much less than their upward pay comparison were dissatisfied with their pay level. The highest levels of pay level satisfaction were observed when actual pay was congruent with the upward comparison pay level. There was also evidence that individuals who were paid much more than their upward pay comparison were dissatisfied with their pay level. However, the negative effects of overreward on pay satisfaction were considerably smaller than were those of underreward.